Telemedicine pharmacy services implementation in organ transplantation at a metropolitan academic medical center. (July 2018) - Jandovitz, Nicholas; Li, Hanlin; Watts, Brady; Monteiro, Jonathan; Kohlberg, Diana; Tsapepas, Demetra
Transplant patients represent a complex patient population for which telemedicine may allow enhanced access to the healthcare team and promote active engagement in health improvement. This retrospective study summarizes a multi-pronged approach that was instituted to implement a pharmacy telemedicine practice at our institution. Telemedicine visits included the provision of six key elements for our patients: (1) medication reconciliation, (2) vaccination history, (3) medication teaching, (4) pharmacotherapy review, (5) medication adherence, and (6) triage to other providers. From January through June 2017, 46 patients were registered for a visit (recipients n = 32 and living donors n = 14). Three-fourths of the patients who completed a visit connected using a mobile device. Time from discharge to the visit was 5.4 days. The average visit duration was 11.6 ± 8 minutes. Medication reconciliation was performed for 24 patients where 6 (25%) required medication list adjustments. An average of 1.2 ± 0.4 medication changes were updated in the medical record. During visits, patients were asked questions to assess adherence to their regimen, all patients responded favorably indicating that they were following instructions provided by the healthcare team. Telemedicine has the potential to improve the healthcare delivery model by providing increased patient-to-healthcare team interactions and access, which optimize engagement and outcomes.